Investigating enhanced electrical conductivity for antenna applications through dual metallization on 3D printed SLA substrates - Adam, Ahmad Nurhelmy; Yahaya, Irfan; Abu Bakar, Ahmad Adnan; Abdullah, Shahino Mah; Tamchek, Nizam; F. Alforidi, Ahmad; Alahmadi, Ahmed; Jamaluddin, Mohd Haizal; Mohd Azmi, Mohd Azraie; Mohd Ghazali, Mohd Ifwat (Elsevier, 2024)
The advancement of 3D printing (additive manufacturing) has gained interest in variety of applications, especially for antenna fabrication. The demand for cheap, reliable, and high-performance antenna fabrication methods is essential in order to cope with the demand of wireless communications industry. In this work, the focus was emphasized on enhancing the electrical conductivity of the 3D printed substrates fabricated by stereolithography (SLA) 3D printer. The 3D printed substrate went through a dual metallization approach, involving sputtering and electrodeposition techniques for the fabrication of conductive metal layers. The parameters for the sputtering were fixed for all the substrate while current density during electrodeposition process was varied at 25 %, 50 %, 75 % and 100 % from recommended value of current. The results showed that the current density during the electrodeposition determined the conductivity performance of the metal layers and established a significant correlation with the surface morphological. Three different frequencies comprised of 2.4 GHz, 3.5 GHz and 5.0 GHz were selected to simulate and fabricate a microstrip patch antenna using the optimized current density which was valued optimal at 75 % (52.5 mA). The percentage of accuracy between simulated and measured frequencies of antenna, portrayed that the measured values were slightly higher than the simulated approximately about 5.14 to 6.67 %. Therefore, the integration of additive manufacturing or 3D printing techniques for antenna could address the critical necessity for fast and economical solution in wireless systems.